Online Advising Pilot at the Community College of Vermont - Nolan, Kimberly (Online Learning, 2013)
ABSTRACT/KEYWORDSAs more colleges add online courses and fully online programs, the need to offer online supports to students becomes more apparent. The connection to an adviser is critical for all students, but for online students it can serve as their primary connection to the institution (Lorenzetti, 2004). In Fall 2011 a pilot study was conducted at the Community College of Vermont (CCV) to examine online advising through a Moodle course site. Although this pilot study represented a small online advising cohort, 56 of the total 155 online students, it illustrates implications for practice and research. The advising cohort showed a slightly higher retention rate than the overall online population. Based on survey results students reported a strong desire for an adviser who stays with them throughout their educational career at the college. In Fall 2012, CCV institutionalized online advising and began a systematic approach to assisting online students. Five advisors added online students to their work assignments and all CCV advisors were informed of what services CCV would be offering online. When students applied to CCV and selected online (ONL) as a home location, they were contacted via email with an explanation of the online services available to them so that students could make a more informed decision about their home location. In Fall 2012, 286 students selected ONL as their home location and were contacted by staff , 256 students chose to remain online. Keywords: online, advising, community college